PAHAM KETUHANAN DALAM TRADISI LEFA NUANG DESA LAMALERA - Lewar, Theodorus Trichinas Payong; Lelaona , Marselinus Kalang; Terong , Ronaldino Klaudius; Agus Widodo (JAPB: Jurnal Agama, Pendidikan dan Budaya, 2026)
This study examines the concept of divinity within the Lefa Nuang tradition practised by the Lamalera community in Lembata Regency, East Nusa Tenggara. This tradition is a ritual marking the opening of the fishing season which not only holds cultural significance but also possesses a strong religious dimension through the integration of local customs and the Catholic faith. The focus of this study is to explore how the Lamalera community understands and actualises the concept of divinity within the practice of lefa nuang. The methods employed include a literature review using a qualitative approach, as well as interviews with community leaders. The research findings indicate that the Lamalera community views God as the ruler of the sea, the provider of sustenance, and the sustainer of life, present within a harmonious relationship between humans, nature, and ancestors. Furthermore, there is a harmony between traditional rites and Church liturgy that strengthens the community’s religious consciousness. This tradition also embodies theological and social values such as solidarity, dependence on divine providence, and responsibility towards nature. Therefore, the lefa nuang tradition can be understood as an expression of contextual faith that sustains the relationship between God, humanity, and creation within the life of the Lamalera community.